Moment that Goes Beyond Silence: Parents' Lived Experiences of Grief Due to Traumatic Loss in Bataan, Philippines - Jayvie Villazor; Rosalito De Guzman (Camarines Sur Polytechnic Colleges, 2022)
Existing evidence suggests that adverse effects are numerous after a traumatic event. This research aims to validate that by revealing the lived experiences of trauma survivors over the span of two years. A descriptive phenomenological approach was used to accomplish this goal. For data collection, face-to-face and virtual semi-structured interviews were used. The researchers interviewed thirteen parents who had tragically lost a child due to homicide, murder, suicide, or a traffic accident. Four themes appear to emerge, with 17 subthemes. The five subthemes of hurting are behavioral dysfunction, affective destruction, biological pain, cognitive disruption, and interpersonal conflict. Meanwhile, coping has five subthemes: emotion-focused, social interaction-focused, digital-focused, behavior-focused, and cognitive-focused. The growing theme is composed of five subthemes: interpersonal enhancement, life appreciation, spiritual growth, parenting actualization, and insight imparting. The remembering theme is divided into two themes, the presence, and absence of the deceased child. Though limited, this study can nonetheless serve as the country's first to focus on grief by traumatic loss. It will serve as additional knowledge in the fields of psychotraumatology, thanatology, positive psychology, and suicidology in the Philippines. Clinicians and other mental health care providers would benefit from the information based on their own experiences as grieving parents. Additionally, research ideas are provided. Indeed, this paper proves that a survivor can not just experience the negative impacts but also grow personally from one of the most traumatic events in human experience.